Galectin-3 for prediction of cardiac function compared to NT-proBNP in individuals with prediabetes and type 2 diabetes mellitus - Schmitt, Volker H.; Prochaska, Jürgen; Föll, Annegret Susanne; Schulz, Andreas; Keller, Karsten; Hahad, Omar; Koeck, Thomas; Troebs, Sven-Oliver; Rapp, Steffen; Beutel, Manfred; Pfeiffer, Norbert; Strauch, Konstantin; et al. (Scientific reports, 2021)
Use of galectin-3 for assessing cardiac function in prediabetes and type 2 diabetes mellitus (T2DM) needs to be established. Within the Gutenberg Health Study cohort (N = 15,010, 35-74 years) patient characteristics were investigated regarding galectin-3 levels. Prognostic value of galectin-3 compared to NT-proBNP concerning cardiac function and mortality was assessed in individuals with euglycaemia, prediabetes and T2DM in 5 years follow-up. Higher galectin-3 levels related to older age, female sex and higher prevalence for prediabetes, T2DM, cardiovascular risk factors and comorbidities. Galectin-3 cross-sectionally was related to impaired systolic (beta - 0.36, 95% CI - 0.63/- 0.09; P = 0.008) and diastolic function (beta 0.014, 95% CI 0.001/0.03; P = 0.031) in T2DM and reduced systolic function in prediabetes (beta - 0.34, 95% CI - 0.53/- 0.15; P = 0.00045). Galectin-3 prospectively related to systolic (beta - 0.656, 95% CI - 1.07/- 0.24; P = 0.0021) and diastolic dysfunction (beta 0.0179, 95% CI 0.0001/0.036; P = 0.049), cardiovascular (hazard ratio per standard deviation of galectin-3 (HRperSD) 1.60, 95% CI 1.39-1.85; P < 0.0001) and all-cause mortality (HRperSD 1.36, 95% CI 1.25-1.47; P < 0.0001) in T2DM. No relationship between galectin-3 and cardiac function was found in euglycaemia, whereas NT-proBNP consistently related to reduced cardiac function. Prospective value of NT-proBNP on cardiovascular and all-cause mortality was higher. NT-proBNP was superior to galectin-3 to assess reduced systolic and diastolic function.
Gesehen am 02.12.2021